(untitled) - Vaculik, Juraj; Monosi, Michal (Doprava a spoje, 2010)
This paper deals with efectivity of contact centres and deals with methods how to increase efectivity. In this paper are listed possibilities how to increase efectivity of contact centres with teoretical examples of performance increasing, in this article are listed also negative results.